Dermatoses in the AIDS - Acebes, L Olmos (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2001)
The authors report shortly on their experience in diagnosing and treating skinmanifestations in the early and late stages of HIV infection. They believethat by careful observation of skin symptoms it is possible to suspect with great probability the HIV infection. According to their experience they range the symptoms into three major groups. The most frequent disorders: seborrheic dermatitis, candidiasis, condyloma accuminatum, herpes simplex, Kaposis sarcoma, and dermatophytosis. Dermatoses with aggressive course: syphilis, cutaneous leishmaniasis, necrotising folliculitis, necrotising gingivitis, herpes zoster, molluscum contagiosum, scabies and papular pruriticeruption. Exceptional dermatoses: psoriasis, oral hairy leukoplakia, and prurigo. This review was prepared in order to help the dermatologists and general practitioners in screening the HIV positive patients.
Keywords: Acquired immunodeficiency syndrome; AIDS; bolniki; Candidiasis; Condylomata acuminata; dermatitis; Dermatitis, seborrheic; dermatologija; Dermatomycoses; Diagnosis; Drug therapy; Folliculitis; Gingivitis, necrotizing ulcerative; Herpes simplex; Herpes zoster; Hiv seropositivity; kožne bolezni; Molluscum contagiosum; Prurigo; Pruritus; Sarcoma, kaposi's; Scabies; Skin diseases; Therapy